Geometric Design of Coordinated Traffic Signal Intersections: Case Study of Four-Way Intersections at Kapuas II Bridge and Kapur Village - Zulkarnaen, Dedy; Mayuni, Siti; Mukti, Elsa Tri; Nurhayati, Nurhayati (Fakultas Teknik Universitas Tanjungpura, 2024)
The four-way intersections at Kapuas Bridge II, Jalan Mayor Alianyang